Methodological deficits in diagnostic research using '-omics' technologies: evaluation of the QUADOMICS tool and quality of recently published studies. - Lucy A Parker (Public Library of Science (PLoS), 2010)
Background QUADOMICS is an adaptation of QUADAS (a quality assessment tool for use in systematic reviews of diagnostic accuracy studies), which takes into account the particular challenges presented by '-omics' based technologies. Our primary objective was to evaluate the applicability and consistency of QUADOMICS. Subsequently we evaluated and describe the methodological quality of a sample of recently published studies using the tool. Methodology/principal findings 45'-omics'-based diagnostic studies were identified by systematic search of Pubmed using suitable MeSH terms ("Genomics", "Sensitivity and specificity", "Diagnosis"). Three investigators independently assessed the quality of the articles using QUADOMICS and met to compare observations and generate a consensus. Consistency and applicability was assessed by comparing each reviewer's original rating with the consensus. Methodological quality was described using the consensus rating. Agreement was above 80% for all three reviewers. Four items presented difficulties with application, mostly due to the lack of a clearly defined gold standard. Methodological quality of our sample was poor; studies met roughly half of the applied criteria (mean +/- sd, 54.7+/-18.4%). Few studies were carried out in a population that mirrored the clinical situation in which the test would be used in practice, (6, 13.3%); none described patient recruitment sufficiently; and less than half described clinical and physiological factors that might influence the biomarker profile (20, 44.4%). Conclusions The QUADOMICS tool can consistently be applied to diagnostic '-omics' studies presently published in biomedical journals. A substantial proportion of reports in this research field fail to address design issues that are fundamental to make inferences relevant for patient care.